O embrulho como metáfora em Quase memória, de Carlos Heitor Cony - Silva, Camile Antunes da (2021)
In this study, I approach reading as a relationship between the reader and the text, working this concept based on my own relationship with the work Quase memória (1995) by the Brazilian writer Carlos Heitor Cony. At first, I tell how reading the narrative made me realize the package that Cony (main character and narrator) receives in the story, not just as an object that reminds him of a series of memories with his father, but mainly as an item full of meanings. Next, I report the connections that the package established with my readings and several other readings that emerged throughout the research process. So, I reflect on what was born from my reading process, it means, the perception of the package as a metaphor, as a way of creating experience and how the reading process itself is a continuous experience.